Living Architecture: Toward Energy Generating Buildings Powered by Microbial Fuel Cells - You, Jiseon; Rimbu, Gimi A.; Wallis, Lauren; Greenman, John; Ieropoulos, Ioannis (Frontiers in Energy Research, 2019)
In this study, possibilities of integrating microbial fuel cell (MFC) technology and buildings were investigated. Three kinds of conventional house bricks from two different locations were tested as MFC reactors and their electrochemical characteristics were analysed. European standard off-the-shelf house bricks generated a maximum power of 1.2 mW (13.5 mW m−2) when fed with human urine. Ugandan house air bricks produced a maximum power of 2.7 mW (32.8 mW m−2), again with human urine. Different cathode types made by surface modifications using two kinds of carbon compounds and two PTFE based binders were tested in both wet and dry cathode conditions. The effects of both anode and cathode sizes, electrode connection, electrode configuration, and feedstock on brick MFC power generation were also studied. Water absorption test results showed higher porosity for the Ugandan air bricks than European engineering bricks, which contributed to its higher performance. This study suggests that the idea of converting existing and future buildings to micro-power stations and micro-treatment plants with the help of integrated MFCs and other renewable technologies is achievable, which will be a step closer to a truly sustainable life.